1997
DOI: 10.1183/09031936.97.10051008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a novel orally active selective PDE4 isoenzyme inhibitor (CDP840) on allergen-induced responses in asthmatic subjects

Abstract: Recent studies have suggested that theophylline, a nonspecific phospho-diesterase inhibitor, has useful anti-inflammatory actions in asthma. Phosphodiesterase 4 (PDE4) represents the predominant PDE isoenzyme present in inflammatory cells. PDE4 inhibitors might, therefore, have beneficial effects in asthma. Sideeffects, specifically nausea, have limited the use of existing agents. CDP840 is an orally active, potent and selective PDE4 inhibitor. We have examined the effect of CDP840 on the allergen-induced asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 43 publications
2
45
0
1
Order By: Relevance
“…In this study, we focus on the mechanistic profile of inhibition at the enzyme and inflammatory cytokine level. The compound that has been profiled is L-826,141, which is a structural analog to CDP840, which has previously demonstrated attenuation of the late asthmatic response in humans in an allergen challenge paradigm (Harbinson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on the mechanistic profile of inhibition at the enzyme and inflammatory cytokine level. The compound that has been profiled is L-826,141, which is a structural analog to CDP840, which has previously demonstrated attenuation of the late asthmatic response in humans in an allergen challenge paradigm (Harbinson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also shown efficacy for other orally administered PDE4 selective inhibitors on relevant asthma endpoints such as inhibition of allergen challenge [9,10] and exercise induced bronchoconstriction [11], as well as improvements in lung function [12]. However, the tolerability of these orally administered drugs is limited by side effects such as gastro-intestinal symptoms [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a number of PDE4 inhibitors have been shown to have an anti-inflammatory activity clinically [38,48,49], which is thought to contribute to a long-term improvement in lung function and fewer exacerbations in patients with severe COPD, as has been observed with the recently approved PDE4 inhibitor, roflumilast N-oxide [50,51], although the side-effect profile of this drug still limits the wider use of this agent. However, while PDE4 is found in human airway smooth muscle, it is now clear from a number of clinical studies with a variety of PDE4 inhibitors administered either orally [52,53] or by inhalation [54], that this drug class is not able to induce acute bronchodilation [38]. In contrast, a number of selective PDE3 inhibitors have been shown to be bronchodilators in man [55,56] and, indeed, recently, PDE3 has been documented to be upregulated in airway smooth muscle obtained from patients with asthma [57].…”
Section: Bifunctional Bronchodilator/anti-inflammatory Drugsmentioning
confidence: 99%